Green Innovation as a Key Mediator in Green Supply Chain Practices: Evidence from Fashion SMEs - R Deni Muhammad Danial; Abdul Bari; Tetty Sufianty Zafar (Jurnal Ilmiah Manajemen Kesatuan, 2026)
In response to increasing global pressure for environmental sustainability, businesses are required to integrate environmentally friendly practices throughout their supply chains. This study aims to analyze the effect of green innovation in mediating the influence of top management commitment and knowledge management orientation on green supply chain management practices in fashion SMEs. The approach used is explanatory quantitative, with 100 SME respondents analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The findings show that top management commitment significantly influences green innovation but not green supply chain management practices directly. Knowledge management orientation significantly affects green supply chain management practices, but not green innovation. Furthermore, green innovation mediates the relationship between top management commitment and green supply chain management practices, but not knowledge management orientation. These findings suggest that leadership commitment should be effectively translated into innovative environmental initiatives to strengthen sustainable supply chain practices. This study provides theoretical implications for the development of sustainable management models and practical implications for SMEs in strengthening green economy-based business strategies.